Preliminary Phyto-chemical screening of Abelmoschusesculentus Linn. - Pranabesh Chakraborty2, Kamalesh Purkait1*, Subrata Das1, Tamal Maity2 (Journal of Biomedical and Pharmaceutical Research, 2017)
Herbal drugs with little or no adverse effects are becoming a necessity in our daily life. The herbal products & herbal drug extracts are now a day’s being used extensively for the preparation of pharmaceutical dosage forms as well as cosmeceuticals. In these work plant parts of Abelmoschus esculentus (Okra) were authenticated by appropriate authority. The dried pods of Abelmoschus esculentus (Okra) were extracted with various solvents or combination of solvents by maceration. Several chemical tests were performed on these extracts of the crude drugs. Some tests gave positive results. Some physical tests like loss on drying were conducted. Total phenolic & total flavonoid content were also determined. Different protocols were followed for the screening procedures, references of which were also provided.Keywords:Abelmoschus esculentus (Okra), Malvaceae, botanical evaluation, phyto-chemicals, extractive values